Testing for Poisson arrivals in INAR(1) processes - Schweer, Sebastian; Weiß, Christian (TEST, 2016)
In the framework of integer-valued autoregressive processes of order 1 [INAR(1)], two new tests for the null hypothesis of Poisson-distributed innovations are developed. The tests focus on time reversibility, as this feature is shown to be satisfied exclusively by Poisson INAR(1) processes. The necessary asymptotic variances are explicitly calculated using the joint cumulants of these processes. The finite-sample behavior of the test statistics and the power of the tests are investigated in a simulation study. The results show that the newly developed tests perform better than existing ones in certain situations.
Published online: 7 December 2015
Gesehen am 01.06.2018